The most dangerous animal of all : searching for my father ... and finding the Zodiac Killer - Stewart, Gary L. (Harper, 2014)
"An explosive and historic book of true crime and an emotionally powerful and revelatory memoir of a man whose ten-year search for his biological father leads to a chilling discovery: His father is one of the most notorious--and still at large--serial killers in America. Soon after his birth mother contacted him for the first time at the age of thirty-nine, adoptee Gary L. Stewart decided to search for his biological father. It was a quest that would lead him to a horrifying truth and force him to reconsider everything he thought he knew about himself and his world. Written with award-winning author and journalist Susan D. Mustafa, The Most Dangerous Animal of All tells the story of Stewart's decade-long search for his father following a complex trail of startling twists and connections. Combing through government records and news reports and through conversations with his father's relatives and friends, Stewart turns up a host of clues, including forensic evidence, identifying his father as one of the most infamous and still-wanted serial killers in American history"--Publisher description.